(untitled) (Bangladesh Journal of Medical Science, 2016)
Sarcoidosis is a chronic granulomatous disease of unknown etiology which principally affects the lower respiratory tract & lungs. Sarcoidosis in the head & neck region is infrequent. Isolated sino nasal sarcoidosis without pulmonary involvement is rare. Case: An 18 years old male patient presented with the complaints of nasal blockage, purulent nasal discharge which was occasionally blood stained for 6 months, deformity of nose, swelling of face & lips for 4 months & watering of eyes for same duration. Endoscopy of nose revealed intra nasal mucosal thickening which was friable & bleeds on touch. The diagnosis of sino nasal sarcoidosis was made by histopathological examination of nasal biopsy specimen. Conclusion: Sino nasal sarcoidosis is a disease of diagnostic challenge to the clinician as its mimicking clinical features may be misleading & cause delay in definitive diagnosis. In the current case report, we presented a case of sino nasal sarcoidosis presenting as chronic rhino sinusitis. Bangladesh Journal of Medical Science Vol.15(4) 2016 p.648-650